Revolt in Palestine in the eighteenth century - Joudah, Ahmad Hasan. (Piscataway, NJ)
xiv, 230 sayfa
Keywords: “In the turbulent atmosphere of the eighteenth century when the Ottoman Empire was enfeebled, local leaders far from Istanbul took matters into their own hands. At first, these leaders only regulated local trade and tax collection, but soon, leaders like Shaykh Zahir al-‘Umar — a district tax collector in Palestine— saw opportunities to amass great wealth and power while providing autonomous government and safer roads to their local followers. A gripping and fascinating read, Ahmad Joudah’s biography of Shaykh Zahir is crucial for scholars seeking to contextualize developments in modern Palestinian history within the politics of the late Ottoman Empire“ -- Yayıncı.